Lid wiper epitheliopathy: an early sign of dry eye diagnosis - Gao, Yuan; Huang, Meiting; Song, Wenjing; Li, Yingsi; Yan, Xiaoming (Frontiers in Medicine, 2025)
ObjectivesThe purpose of this study was to investigate the relationship between the severity of lid wiper epitheliopathy (LWE) and ocular surface features and evaluate the potential of LWE as an early diagnosis indicator of dry eye.MethodsEighty-eight patients diagnosed with dry eye by TFOS DEWS II were divided into two groups based on the Korb grading: the mild group and the moderate–severe group. Ocular assessments included examination of LWE, tear-film lipid layer thickness (LLT) measurement, partial blinking rate (PBR) calculation, fluorescein tear breakup time (FTBUT) measurement, determining corneal fluorescein staining score, eyelid margin score, and meiboscore.ResultsIn patients with upper LWE, the PBR and ocular surface disease index (OSDI) score were higher and LLT was lower in the moderate–severe LWE group (p < 0.05). In patients with lower LWE, the PBR and lower eyelid margin score were significantly higher in the moderate–severe LWE group (p < 0.05). The upper LWE staining score was moderately and significantly associated with the lower LWE staining score. Compared with LWE, if the FTBUT was used as the diagnostic indicator according to TFOS DEWS II, China, or ADES, the missed diagnosis rate fluctuated from 5.7 to 54.5%.ConclusionThe severity of LWE is related to dry eye indicators such as the PBR, FTBUT, eyelid margin score, OSDI, and meiboscore. Both upper and lower LWE can be used as diagnostic criteria for dry eye. Moreover, compared with FTBUT, LWE is more suitable as an early sign of dry eye diagnosis.